Fungal Biota and Mycotoxins Contamination in Soybean Expeller - Maciel, Gisele; Castellari, Claudia; Cardoso, Marcelo Leandro; Abadia, María Bernadette; Busato, Patrizia; Bartosik, Ricardo Enrique (MDPI, 2025)
Soybean expeller (SBE), a by-product of soybean oil extraction through the extruding-expelling process, is widely used as a protein source in animal feed and soy-based foods. This study evaluated fungal contamination and mycotoxin levels in SBE samples from 11 extruding-expelling facilities in Argentina, assessing fungal load, moisture content (MC), and mycotoxin profiles. Fungal biota was quantified through colony forming unit (CFU) counts and identified via morphological analysis, while mycotoxins were quantified using liquid chromatography and tandem mass spectrometry. CFU counts were low (0 to 4 CFU g−1 DM), with Penicillium spp. (28.0%) and Mucoraceae (family) (25.6%) being the most frequently isolated genera. Deoxynivalenol (DON) and aflatoxins (AFB1, AFB2, AFG1, and AFG2) were detected in 20% to 40% of the samples. The average concentration was 215.19 µg kg−1 for DON and 41.68, 0.39, and 0.34 µg kg−1 for AFB1, AFG1, and AFG2, respectively. Although most mycotoxin concentrations were below regulatory limits, a few samples exceeded the threshold for DON (8.6%) and AFB1 (2.9%). Co-occurrence of two mycotoxins was observed in 60% of the samples. These results highlight the importance of monitoring fungal contamination and mycotoxin levels to ensure the safety and quality of SBE for feed and food applications.